P486 Population structure of Lymphogranuloma venereum in belgium: surveillance data from 2010 until 2017. (14th July 2019) - Baetselier, Irith De; Cuylaerts, Vicky; Smet, Hilde; Abdellati, Saïd; Deken, Bénédicte De; Thys, Wendy; Meehan, Conor; Crucitti, Tania
Abstract : Background: The number of Chlamydia trachomatis (CT) L genotypes/serovars or Lymphogranuloma venereum (LGV) is on the rise in Belgium, however the genetic diversity of the CT L genotypes in Belgium remained unknown. Our aim was to document the population structure of the LGV cases over the years. Methods: The complete outer membrane protein A gene ( ompA ) of remnant positive LGV samples (previously confirmed by an in-house qPCR; target: pmpH gene) was amplified and sequenced using automated DNA sequencing. The obtained aligned sequences were compared with all L-variants described in literature and with all CT ompA sequences using the BLAST search. Results: All samples were from men who have sex with men; mostly HIV positive (82.2%) and from anorectal origin (94.1%). Sequencing of ompA (n=118) revealed that, in total, L2 and L2b genotypes were equally found (42.4%) followed by variants of L2 genotypes: L2bV2(6.8%) and L2bV1 (3.4%). Curiously, one strain defined as L2a had one additional mutation (A515C – Lys172Thr) which is also found in L2bV2 (hereafter named L2aV2). Three L1 strains were identified over the years (one in 2016 and two in 2017) but no link between the three could be found. Two strains could not be characterized due to mixed infection with non-L genotypes. Most of infections were symptomatic (80.7%) with proctitis (71.1%) as predominant symptom. Re-infections were common in our population (9.3%) and sequencing showed that individuals could become infected by different strains in a short period of time. No significant association was found between HIV status, presence of symptoms and the L-genotypes. Conclusion: The LGV strains in Belgium are more genetically diverse than initially thought as a total of two L-variants and five L2-genotypes have been identified. No firm conclusions can be made concerning an association between clinical symptoms and specific L-genotypes as asymptomatic infections were found with all L2 variants. Disclosure: No significant relationships.